Lithium battery diaphragm with high coating peel strength and preparation method thereof

By using porous PVA@PVDF composite coating on the lithium battery separator, the existing separator is easily short-circuited and poor electrolyte adsorption properties are solved, and the safety and performance of the existing separator is achieved at high temperatures, which is achieved with higher thermal stability and electrolyte adsorption capabilities, and the safety and performance of the lithium battery are improved.

CN119812665AActive Publication Date: 2025-04-11HARBIN INST OF TECH ZHENGZHOU RES INST
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510096658.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-22
Publication Date
2025-04-11
Estimated Expiration
2045-01-22

AI Technical Summary

Technical Problem

Existing lithium battery separators are prone to short-circuiting the battery at high temperatures, and have poor adsorption of the electrolyte, affecting the conduction of lithium ions.

Method used

Porous PVA@PVDF composite material is used as the coating material, and the slurry is coated by uniformly rolling the porous PVA@PVDF composite material on the polyolefin separator, and baked at 70~75°C to be rolled into a lithium battery separator.

Benefits of technology

It significantly improves the adhesion of the separator and the wetting properties of the electrolyte, improves the thermal stability of the separator and the adsorption ability of the electrolyte, and enhances the safety and performance of lithium batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention relates to the technical field of lithium battery diaphragms, and discloses a lithium battery diaphragm with high coating peel strength and a preparation method thereof. Comprising the following operation steps: S1, premixing a porous PVA (at) PVDF composite material with ultrapure water, adding a binder, uniformly mixing, adding a wetting agent, and uniformly mixing to obtain porous PVA (at) PVDF composite material coating slurry; and S2, uniformly roller-coating the porous PVA-coated PVDF composite material coating slurry on a polyolefin diaphragm, baking at 70-75 DEG C, and rolling to obtain the lithium battery diaphragm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium battery separators, in particular to a lithium battery separator with high coating peeling strength and a preparation method thereof. Background Art

[0002] Lithium battery separators are insulating materials that separate the positive and negative electrodes of the battery, allowing lithium ions to move between the positive and negative electrodes through the separator; therefore, the quality of the separator has a direct impact on the performance of the lithium battery, and even indirectly affects the safety of the lithium battery. The commercial separators mainly include polyolefin separators (polyethylene PE, polypropylene PP, composite film PP / PE / PP) and non-woven fabrics. Polyolefin separators have the advantages of good mechanical properties, low price and non-toxicity, and are widely used in lithium batteries.

[0003] However, commercial microporous membranes shrink due to closed pores near the melting temperature, causing battery short circuits and making lithium batteries prone to combustion and explosion at high temperatures. In addition, polyolefin separators have poor adsorption of electrolytes, which is not conducive to the conduction of lithium ions during charging and discharging. Studies have found that inorganic nanoparticle coatings and polymer porous coatings have higher thermal stability and stronger electrolyte adsorption capacity, thereby improving the thermal stability and electrolyte adsorption of composite separators.

[0004] In order to solve the problem of poor electrode adhesion and electrolyte wettability of polyolefin diaphragms, the current main solution is to coat a water-based PVDF adhesive layer on one or both sides of the diaphragm; this coating layer can effectively improve the adhesion performance of the diaphragm and has good wettability with the electrolyte; however, since PVDF itself is hydrophobic, it cannot be directly dispersed in water; therefore, in the prior art, the preparation of PVDF slurry requires the addition of a large amount of additives, or even a variety of different additives, to ensure that it can be evenly dispersed in water; however, the preparation process is cumbersome and time-consuming, and it also greatly reduces production efficiency, increases production costs, and thus compresses the profit margin of the diaphragm; therefore, the development of a highly adhesive and easy-to-prepare water-based PVDF coated diaphragm has become a common goal pursued by the industry. Summary of the invention

[0005] The object of the present invention is to provide a lithium battery separator with high coating peeling strength and a preparation method thereof, so as to solve the problems raised in the prior art.

[0006] To achieve the above object, the present invention provides the following technical solutions: A method for preparing a lithium battery separator with high coating peel strength comprises the following steps: S1: premixing the porous PVA@PVDF composite material with ultrapure water, adding a binder and mixing evenly, and then adding a wetting agent and mixing evenly to obtain a porous PVA@PVDF composite material coating slurry; S2: Roll-coat the porous PVA@PVDF composite material coating slurry evenly on the polyolefin separator, bake at 70-75°C, and roll it up to obtain a lithium battery separator.

[0007] More optimally, the raw materials of the porous PVA@PVDF composite material coating slurry include the following components: by mass percentage, 5~15wt% porous PVA@PVDF composite material, 2~11wt% binder, 0.1~0.7wt% wetting agent, and the rest is ultrapure water.

[0008] More optimally, the coating surface density of the porous PVA@PVDF composite material coating slurry on the lithium battery separator is 0.7±0.1g / m 2 .

[0009] In the scheme, the porous PVA@PVDF composite material coating slurry is coated on the polyolefin membrane on both sides or one side.

[0010] More optimally, the binder is polyacrylonitrile and the wetting agent is polyether silicone.

[0011] The preparation method of the porous PVA@PVDF composite material is more optimized as follows: (1) adding PVDF powder to ultrapure water and mixing uniformly to obtain a PVDF suspension; (2) adding polyvinyl alcohol to formamide for sealing, mixing at a temperature of 35-40°C for 5-7 hours to obtain a polyvinyl alcohol solution; (3) first slowly adding the polyvinyl alcohol solution to the PVDF suspension at a flow rate of 0.7-0.85 ml / min under stirring and ultrasonic treatment conditions; then reducing the speed to 700-750 rpm, mixing for 2-3 hours, and ultrasonic treatment for 4-6 hours to obtain a mixed solution; centrifuging, washing, and vacuum drying the mixed solution to obtain a porous PVA@PVDF composite material.

[0012] More optimally, the raw materials of the porous PVA@PVDF composite material include the following components: 4 to 5 parts of PVDF powder, 1.5 to 2.5 parts of polyvinyl alcohol, 250 to 300 parts of ultrapure water, and 8 to 10 parts of formamide, by mass.

[0013] More optimally, the stirring speed is 1000-12000 rpm; the power of the ultrasonic treatment is 350-450 W, and the frequency is 30-45 KHz.

[0014] More optimally, the vacuum degree of the vacuum drying is 0.05-0.08 MPa, the temperature is 60-65° C., and the drying time is 40-48 hours.

[0015] Compared with the prior art, the present invention has the following beneficial effects: The present invention provides a composite diaphragm modified with a porous PVA@PVDF composite material; PVA is a high polymer containing a large amount of hydroxyl groups, and the hydroxyl group is a strong hydrophilic group. The modification of PVDF with porous PVA can significantly improve the problem that PVDF is difficult to disperse in water. The modified PVDF can be directly and well dispersed in water, and the slurry preparation process is very simple, thereby greatly improving the production efficiency and reducing the production cost, thereby greatly increasing the profit margin of the diaphragm.

[0016] The introduction of PVDF can effectively improve the adhesion of the diaphragm and its wettability with the electrolyte; in addition, PVA has good adhesion, and the introduction of PVA further improves the adhesion performance of the diaphragm; the PVA@PVDF composite material in the scheme has a porous structure, which can improve the air permeability of the PVDF coating film, and the polyether silicone wetting agent has good mechanical properties, heat resistance and wettability, thereby improving the hot pressing peeling performance of the diaphragm. DETAILED DESCRIPTION

[0017] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0018] In the following specific embodiments, parts are by mass. In this embodiment, it should be noted that the purchase manufacturers of all raw materials involved in the present invention are not subject to any special restrictions, and exemplary examples include: PVDF powder model LBG-8200, purchased from Arkema; ​​polyvinyl alcohol (PVA) model 2699, purchased from Shenzhen Boshun Chemical Co., Ltd.; polyolefin diaphragm material is polyethylene, purchased from Shenzhen Liyou New Energy Technology Co., Ltd.; binder (polyacrylonitrile) model LA133, purchased from Hubei Maidehao Biotechnology Co., Ltd.; wetting agent (polyether silicone) model WE3220, purchased from Shanghai Zhenli Shi Network Technology Co., Ltd.; the thickener is sodium hydroxymethyl cellulose, the product number is S14014, purchased from Yuanye Biotechnology; the defoamer (polyether defoamer) has the product number XP1809C, purchased from Luoyang Xipeng Environmental Protection Technology Co., Ltd.; the dispersant (aliphatic amide dispersant) is vinyl bisstearamide, the CAS number is 110-30-5, purchased from Wuhan Jixin Yibang Biotechnology Co., Ltd.; the binder (polyacrylic acid) is polyacrylic acid, the specification is BR, the molecular weight is 3000, purchased from Shanghai Huzhen Industrial Co., Ltd.; the CAS number of formamide is 75-12-7; the CAS number of polydimethylsiloxane alcohol (average Mn~5600) is 156327-07-0, purchased from McLean.

[0019] Example 1: A lithium battery separator with high coating peel strength and a preparation method thereof, comprising the following steps: S1.1: (1) 4.25 parts of PVDF powder and 280 parts of ultrapure water were placed in a 500 ml three-necked flask, first stirred at 1200 rpm for 120 minutes, and then ultrasonically treated at 45 kHz and 450 W for 12 hours to obtain a PVDF suspension; (2) 1.85 parts of polyvinyl alcohol were added to 8 parts of formamide, sealed, and stirred at 400 rpm for 5 hours at a temperature of 40°C to obtain a polyvinyl alcohol solution; (3) First stirred (speed 1000 rpm) and Under the condition of ultrasonic treatment (frequency 40KHz, power 400w), the polyvinyl alcohol solution was slowly added to the PVDF suspension at a flow rate of 0.85ml / min; then the rotation speed was reduced to 750rpm and stirred for 3 hours, and then ultrasonic treatment (frequency 35KHz, power 450w) was performed for 5 hours to obtain a mixed solution; it was centrifuged at 8500rpm for 20 minutes, washed, and vacuum dried at a vacuum degree of 0.08MPa and a temperature of 60°C for 48 hours to obtain a porous PVA@PVDF composite material; S1.2: premix the porous PVA@PVDF composite material with ultrapure water at a rotation speed of 700 rpm for 90 minutes, add a binder, stir at a rotation speed of 1000 rpm for 40 minutes, reduce the rotation speed to 350 rpm, add a wetting agent and stir for 30 minutes to obtain a porous PVA@PVDF composite material coating slurry; The raw materials of the porous PVA@PVDF composite material coating slurry include the following components: by mass percentage, 5wt% porous PVA@PVDF composite material, 9wt% binder (polyacrylonitrile, LA133), 0.5wt% wetting agent (polyether silicone, WE3220), and the rest is ultrapure water; S2: The porous PVA@PVDF composite material coating slurry is evenly rolled on both sides of the polyolefin separator, and then rolled up after baking in an oven at 75°C to obtain a lithium battery separator.

[0020] Example 2: A lithium battery separator with high coating peel strength and a preparation method thereof, comprising the following steps: S1.1: (1) 4.25 parts of PVDF powder and 280 parts of ultrapure water were placed in a 500 ml three-necked flask, first stirred at 1200 rpm for 120 minutes, and then ultrasonically treated at 45 kHz and 450 W for 12 hours to obtain a PVDF suspension; (2) 1.85 parts of polyvinyl alcohol were added to 8 parts of formamide, sealed, and stirred at 400 rpm for 5 hours at a temperature of 40°C to obtain a polyvinyl alcohol solution; (3) First stirred (speed 1000 rpm) and Under the condition of ultrasonic treatment (frequency 40KHz, power 400w), the polyvinyl alcohol solution was slowly added to the PVDF suspension at a flow rate of 0.85ml / min; then the rotation speed was reduced to 750rpm and stirred for 3 hours, and then ultrasonic treatment (frequency 35KHz, power 450w) was performed for 5 hours to obtain a mixed solution; it was centrifuged at 8500rpm for 20 minutes, washed, and vacuum dried at a vacuum degree of 0.08MPa and a temperature of 60°C for 48 hours to obtain a porous PVA@PVDF composite material; S1.2: premix the porous PVA@PVDF composite material with ultrapure water at a rotation speed of 700 rpm for 90 minutes; add a binder, stir at a rotation speed of 1000 rpm for 40 minutes, reduce the rotation speed to 350 rpm; add a wetting agent and stir for 30 minutes to obtain a porous PVA@PVDF composite material coating slurry; The raw materials of the porous PVA@PVDF composite material coating slurry include the following components: by mass percentage, 10wt% porous PVA@PVDF composite material, 9wt% binder (polyacrylonitrile, LA133), 0.5wt% wetting agent (polyether silicone, WE3220), and the rest is ultrapure water; S2: The porous PVA@PVDF composite material coating slurry is evenly rolled on both sides of the polyolefin separator, and then rolled up after baking in an oven at 75°C to obtain a lithium battery separator.

[0021] Example 3: A lithium battery separator with high coating peel strength and a preparation method thereof, comprising the following steps: S1.1: (1) 4.25 parts of PVDF powder and 280 parts of ultrapure water were placed in a 500 ml three-necked flask, first stirred at 1200 rpm for 120 minutes, and then ultrasonically treated at 45 kHz and 450 W for 12 hours to obtain a PVDF suspension; (2) 1.85 parts of polyvinyl alcohol were added to 8 parts of formamide, sealed, and stirred at 400 rpm for 5 hours at a temperature of 40°C to obtain a polyvinyl alcohol solution; (3) First stirred (speed 1000 rpm) and Under the condition of ultrasonic treatment (frequency 40KHz, power 400w), the polyvinyl alcohol solution was slowly added to the PVDF suspension at a flow rate of 0.85ml / min; then the rotation speed was reduced to 750rpm and stirred for 3 hours, and then ultrasonic treatment (frequency 35KHz, power 450w) was performed for 5 hours to obtain a mixed solution; it was centrifuged at 8500rpm for 20 minutes, washed, and vacuum dried at a vacuum degree of 0.08MPa and a temperature of 60°C for 48 hours to obtain a porous PVA@PVDF composite material; S1.2: premix the porous PVA@PVDF composite material with ultrapure water at a rotation speed of 700 rpm for 90 minutes, add a binder, stir at a rotation speed of 1000 rpm for 40 minutes, reduce the rotation speed to 350 rpm, add a wetting agent and stir for 30 minutes to obtain a porous PVA@PVDF composite material coating slurry; The raw materials of the porous PVA@PVDF composite material coating slurry include the following components: by mass percentage, 15wt% porous PVA@PVDF composite material, 9wt% binder (polyacrylonitrile, LA133), 0.5wt% wetting agent (polyether silicone, WE3220), and the rest is ultrapure water; S2: The porous PVA@PVDF composite material coating slurry is evenly rolled on both sides of the polyolefin separator, and then rolled up after baking in an oven at 75°C to obtain a lithium battery separator.

[0022] Example 4, coating a polyolefin separator on one side; S1.1: (1) 4.25 parts of PVDF powder and 280 parts of ultrapure water were placed in a 500 ml three-necked flask, first stirred at 1200 rpm for 120 minutes, and then ultrasonically treated at 45 kHz and 450 W for 12 hours to obtain a PVDF suspension; (2) 1.85 parts of polyvinyl alcohol were added to 8 parts of formamide, sealed, and stirred at 400 rpm for 5 hours at a temperature of 40°C to obtain a polyvinyl alcohol solution; (3) First stirred (speed 1000 rpm) and Under the condition of ultrasonic treatment (frequency 40KHz, power 400w), the polyvinyl alcohol solution was slowly added to the PVDF suspension at a flow rate of 0.85ml / min; then the rotation speed was reduced to 750rpm and stirred for 3 hours, and then ultrasonic treatment (frequency 35KHz, power 450w) was performed for 5 hours to obtain a mixed solution; it was centrifuged at 8500rpm for 20 minutes, washed, and vacuum dried at a vacuum degree of 0.08MPa and a temperature of 60°C for 48 hours to obtain a porous PVA@PVDF composite material; S1.2: premix the porous PVA@PVDF composite material with ultrapure water at a rotation speed of 700 rpm for 90 minutes, add a binder, stir at a rotation speed of 1000 rpm for 40 minutes, reduce the rotation speed to 350 rpm, add a wetting agent and stir for 30 minutes to obtain a porous PVA@PVDF composite material coating slurry; The raw materials of the porous PVA@PVDF composite material coating slurry include the following components: by mass percentage, 15wt% porous PVA@PVDF composite material, 9wt% binder (polyacrylonitrile, LA133), 0.5wt% wetting agent (polyether silicone, WE3220), and the rest is ultrapure water; S2: The porous PVA@PVDF composite material coating slurry is evenly rolled on one side of the polyolefin separator, and then rolled up after baking in an oven at 75°C to obtain a lithium battery separator.

[0023] Comparative Example 1: Preparation of conventional PVDF-modified polyolefin membrane; S1: (1) Add dispersant to ultrapure water and premix at 600 rpm for 50 minutes; (2) Add conventional PVDF powder and stir at 700 rpm for 120 minutes; (3) Add thickener and stir at 800 rpm for 90 minutes; (4) Add binder and stir at 1000 rpm for 60 minutes; (5) Add wetting agent and stir at 350 rpm for 40 minutes; (6) Add defoamer and stir at 450 rpm for 30 minutes to obtain conventional PVDF coating slurry; The raw materials of conventional PVDF coating slurry include the following components: by mass percentage, 0.95wt% dispersant, 5wt% conventional PVDF powder, 8wt% thickener (sodium hydroxymethyl cellulose), 15wt% binder (polyacrylic acid, molecular weight 3000), 0.7wt% wetting agent (polydimethylsiloxane alcohol), 0.3wt% defoamer (polyether defoamer, XP1809C), and the rest is ultrapure water; S2: Conventional PVDF coating slurry is uniformly coated on both sides of the polyolefin separator by roller coating, and then rolled up after baking in an oven at 75°C to obtain a lithium battery separator.

[0024] Comparative Example 2: No slurry was applied; The polyolefin separator is not coated and is directly used as a lithium battery separator.

[0025] Comparative Example 3 is based on Example 3, except that the wetting agent is replaced with polydimethylsiloxane alcohol; S1.1: (1) 4.25 parts of PVDF powder and 280 parts of ultrapure water were placed in a 500 ml three-necked flask, first stirred at 1200 rpm for 120 minutes, and then ultrasonically treated at 45 kHz and 450 W for 12 hours to obtain a PVDF suspension; (2) 1.85 parts of polyvinyl alcohol were added to 8 parts of formamide, sealed, and stirred at 400 rpm for 5 hours at a temperature of 40°C to obtain a polyvinyl alcohol solution; (3) First stirred (speed 1000 rpm) and Under the condition of ultrasonic treatment (frequency 40KHz, power 400w), the polyvinyl alcohol solution was slowly added to the PVDF suspension at a flow rate of 0.85ml / min; then the rotation speed was reduced to 750rpm and stirred for 3 hours, and then ultrasonic treatment (frequency 35KHz, power 450w) was performed for 5 hours to obtain a mixed solution; it was centrifuged at 8500rpm for 20 minutes, washed, and vacuum dried at a vacuum degree of 0.08MPa and a temperature of 60°C for 48 hours to obtain a porous PVA@PVDF composite material; S1.2: premix the porous PVA@PVDF composite material with ultrapure water at a rotation speed of 700 rpm for 90 minutes, add a binder, stir at a rotation speed of 1000 rpm for 40 minutes, reduce the rotation speed to 350 rpm, add a wetting agent and stir for 30 minutes to obtain a porous PVA@PVDF composite material coating slurry; The raw materials of the porous PVA@PVDF composite material coating slurry include the following components: by mass percentage, 15wt% porous PVA@PVDF composite material, 9wt% binder (polyacrylonitrile, LA133), 0.5wt% wetting agent (polydimethylsiloxane alcohol, Mn~5600), and the rest is ultrapure water; S2: The porous PVA@PVDF composite material coating slurry is evenly rolled onto the polyolefin separator, and then rolled up after being baked in an oven at 75°C to obtain a lithium battery separator.

[0026] Test: The performance comparison of the lithium battery separators prepared in Examples 1 to 4 and Comparative Examples 1 to 3 is shown in Table 1; Table 1

[0027] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing a lithium battery separator with high coating peel strength, characterized in that: The steps include: S1: premixing the porous PVA@PVDF composite material with ultrapure water, adding a binder and mixing evenly, and then adding a wetting agent and mixing evenly to obtain a porous PVA@PVDF composite material coating slurry; S2: Roll-coat the porous PVA@PVDF composite material coating slurry evenly on the polyolefin separator, bake at 70-75°C, and roll it up to obtain a lithium battery separator.

2. The method for preparing a lithium battery separator with high coating peel strength according to claim 1, characterized in that: The raw materials of the porous PVA@PVDF composite material coating slurry include the following components: by mass percentage, 5-15wt% of porous PVA@PVDF composite material, 2-11wt% of binder, 0.1-0.7wt% of wetting agent, and the rest is ultrapure water.

3. The method for preparing a lithium battery separator with high coating peel strength according to claim 1, characterized in that: The coating surface density of the porous PVA@PVDF composite material coating slurry on the lithium battery separator is 0.7±0.1g / m 2 .

4. The method for preparing a lithium battery separator with high coating peel strength according to claim 2, characterized in that: The binder is polyacrylonitrile and the wetting agent is polyether silicone.

5. The method for preparing a lithium battery separator with high coating peel strength according to claim 1, characterized in that: The preparation method of the porous PVA@PVDF composite material is as follows: (1) adding PVDF powder to ultrapure water and mixing uniformly to obtain a PVDF suspension; (2) adding polyvinyl alcohol to formamide for sealing, mixing at a temperature of 35-40°C for 5-7 hours to obtain a polyvinyl alcohol solution; (3) firstly slowly adding the polyvinyl alcohol solution to the PVDF suspension at a flow rate of 0.7-0.85 ml / min under stirring and ultrasonic treatment conditions; then reducing the rotation speed to 700-750 rpm, mixing for 2-3 hours, and ultrasonic treatment for 4-6 hours to obtain a mixed solution; centrifuging, washing, and vacuum drying the mixed solution to obtain a porous PVA@PVDF composite material.

6. The method for preparing a lithium battery separator with high coating peel strength according to claim 5, characterized in that: The raw materials of the porous PVA@PVDF composite material include the following components: 4-5 parts of PVDF powder, 1.5-2.5 parts of polyvinyl alcohol, 250-300 parts of ultrapure water, and 8-10 parts of formamide, calculated by weight.

7. The method for preparing a lithium battery separator with high coating peel strength according to claim 5, characterized in that: The stirring speed is 1000-12000 rpm; the power of the ultrasonic treatment is 350-450w, and the frequency is 30-45KHz.

8. The method for preparing a lithium battery separator with high coating peel strength according to claim 5, characterized in that: The vacuum degree of the vacuum drying is 0.05-0.08 MPa, the temperature is 60-65° C., and the drying time is 40-48 hours.

9. A lithium battery separator prepared according to the method for preparing a lithium battery separator with high coating peel strength according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • A lithium ion battery separator and a preparation method thereof

    CN109037557A

  • Ceramic PVDF mixed coating lithium ion battery diaphragm and preparation method thereof

    CN109346650A

  • Preparation method of inorganic and organic composite coating diaphragm

    CN110660949A

  • High-viscosity PVDF coated diaphragm and preparation method thereof

    CN112795247A

  • Mixed coating composite diaphragm for lithium battery and preparation method of mixed coating composite diaphragm

    CN117154334A